(untitled) (Pravaha, 2018)
This paper ascertains management praxis at Nepalese manufacturing and non-manufacturing firms that are shaping the firms’ decisions and actions in due course of their managerial process activities. In-depth interviews with selected executives from among the respondents and discourse analysis thereof indicate a varied form of managerial practices. The discourse in the areas of organizational change and management praxis concentrated on the adaptation to their environment. It focuses on the role of executives, culture, environmental change, organizational and business legacy in consideration of discontinuity, innovation and social adaptation. Chisquare test of independence and Kendall’s tau-b have been instrumental in interpretation of the associations and relationships of the principal actors of change makers in organizations and businesses. Pravaha Vol. 24, No. 1, 2018, Page: 159-174